A fast building demand response method based on supply–demand coordination for urgent responses to smart grids. (26th November 2019) - Jin, Chen; Yan, Chengchu; Tang, Rui; Cai, Hao; Zeng, Ruixuan
Abstract : Many demand response (DR) measures are available for building air-conditioning systems, which can be categorized as demand-side-based controls and supply-side-based controls. However, due to the limitations of response speed and/or thermal comfort control, existing methods cannot economically and effectively meet the urgent DR requests from grids in emergency situations. This paper proposes a fast building demand response method based on supply-demand-side coordination for urgent responses to smart grids. It combines both the demand-side-based and supply-side-based control measures simultaneously. On the supply side, direct load control actions are employed to provide immediate power reductions. On the demand side, indoor air temperature set-points are adjusted stepwise according to an "incremental schedule" to achieve a uniform indoor temperature rise in different zones. In addition, two performance indexes are newly proposed to evaluate the sacrifice degree of thermal comfort. Measures for avoiding power rebound in post-DR periods are also considered. The proposed DR method is tested as a case study in a virtual building. The results show that through the coordinated control of the supply and demand side, a fast and effective DR (e.g., 18.3% of power reduction) is achieved with a uniform sacrifice of thermal comfort.